Chromogranin A and its fragments as regulators of small intestinal neuroendocrine neoplasm proliferation - Giovinazzo, Francesco; Schimmack, Simon; Svejda, Bernhard; Alaimo, Daniele; Pfragner, Roswitha; Modlin, Irvin; Kidd, Mark (PLOS ONE, 2013)
IntroductionChromogranin A is a neuroendocrine secretory product and its loss is a feature of malignant NEN de-differentiation. We hypothesized that chromogranin A fragments were differentially expressed during NEN metastasis and played a role in the regulation of NEN proliferation. MethodsChromogranin A mRNA (PCR) and protein (ELISA/western blot) were studied in 10 normal human mucosa, 5 enterochromaffin cell preparations, 26 small intestinal NEN primaries and 9 liver metastases. Cell viability (WST-1 assay), proliferation (bromodeoxyuridine ELISA) and expression of AKT/AKT-P (CASE ELISA/western blot) in response to chromogranin A silencing, inhibition of prohormone convertase and mTOR inhibition (RAD001/AKT antisense) as well as different chromogranin A fragments were examined in 4 SI-NEN cell lines. ResultsChromogranin A mRNA and protein levels were increased (37-340 fold, p<0.0001) in small intestinal NENs compared to normal enterochromaffin cells. Western blot identified chromogranin A-associated processing bands including vasostatin in small intestinal NENs as well as up-regulated expression of prohormone convertase in metastases. Proliferation in small intestinal NEN cell lines was decreased by silencing chromogranin A as well as by inhibition of prohormone convertase (p<0.05). This inhibition also decreased secretion of chromogranin A (p<0.05) and 5-HT (p<0.05) as well as expression of vasostatin. Metastatic small intestinal NEN cell lines were stimulated (50-80%, p<0.05) and AKT phosphorylated (Ser473: p<0.05) by vasostatin I, which was completely reversed by RAD001 (p<0.01) and AKT antisense (p<0.05) while chromostatin inhibited proliferation (~50%, p<0.05). ConclusionChromogranin A was differentially regulated in primary and metastatic small intestinal NENs and cell lines. Chromogranin A fragments regulated metastatic small intestinal NEN proliferation via the AKT pathway indicating that CgA plays a far more complex role in the biology of these tumors than previously considered.
Gesehen am 10.02.2020